Firms, boards and gender quotas comparative perspective - Engelstad, Fredrik, 1944-; Teigen, Mari (Comparative social research ;, 2012)
During the last decade gender equality in business life has become a hot topic. One impetus is the recent reform in Norway, prescribing gender quotas to the boards of directors of public companies. Shortly after the Norwegian reform was enacted, several other European countries have adopted similar reforms. This is the only volume where this gender quota reform is thoroughly discussed from an economic, political and philosophical point of view. It looks at whether the economic performance of companies is influenced, positively or negatively. The reasons why it has been embraced in some countries and rejected in others are analyzed. Moreover, viability of the gender quota reform is assessed by comparisons to other political interventions in business life in Scandinavia, of which some have been a failure whereas others have shown themselves as successful. This specific reform also serves as a backdrop to other themes related to gender and business. This volume provides a broad comparative study of the access of women to top positions in business in Europe. It also gives detailed discussions of gender relations in family businesses both in East Asia and in Europe.